Pendidikan Konsumen Generasi Y: Pengaruh Ethnosentrisme, Hedonisme, dan Kelompok Acuan terhadap Preferensi dan Perilaku Pembelian Buah Lokal - Violetta, Putri Claristha; Hartoyo, Hartoyo; Zulbainarni, Nimmi (Jurnal Ilmu Keluarga dan Konsumen, 2018)
The purpose of this research is to examine the influence of ethnocentrism, hedonism, and reference groups to the preferences and purchasing behaviour of local fruit by generation Y. This research is a descriptive research with survey method using questionnaire. The sampling of this research used non-probability sampling and the number of respondents was 200 students from School of Business and Faculty of Economic and Management Bogor Agricultural University that was divided proportionally based on the sample fraction according to the population of each department at the Faculty. The data analysis used Structural Equation Modelling (SEM). The result showed that ethnocentrism had positively significant influence and hedonism had negatively significant influence on generation Y’s preference, consumer preferences had positively significant influence and hedonism had negatively significant influence on generation Y’s purchasing behaviour of local fruit. Reference group had positively but not significant influence on generation Y’s preference and purchasing behaviour of local fruit. Generation Y’s preference and purchasing behaviour of local fruits can be improved by increasing the ethnocentirsm and decreasing the hedonism of generation Y consumer.